Effect of two-stage injection dwell angle on engine combustion and performance characteristics of a common-rail diesel engine fueled with coconut oil methyl esters-diesel fuel blends - Teoh, Yew Heng; Masjuki, Haji Hassan; How, Heoy Geok; Kalam, Md. Abul; Yu, Kok Hwa; Alabdulkarem, Abdullah (Elsevier, 2018)
Diesel engine is widely used as prime mover due to its high thermal efficiency. Usage of renewable biodiesel in diesel engine is also widely studied due to its potential in reducing emission and as a replacement of conventional diesel. Biodiesel performance could be improved by blending it with petroleum diesel besides introducing appropriate injection strategies. In this experiment, the effect of percentage of biodiesel blends and injection strategies such as variations in start of injection (SOI) timing and dwell angle on diesel engine performance were investigated. The test engine used is four-stroke turbocharged direct injection diesel engine. Results show that exhaust emissions, engine performance and combustion characteristics are substantially affected by biodiesel blending ratio and SOI timing but slightly influenced by two-stage injection dwell angle. Biodiesel blends percentage could be raised to improve NOx and smoke emissions. Even though SOI performed at a later timing could reduce NOx emission, smoke emission increased. Dwell angle between two successive injections could be prolonged to lower the effect of the increase in smoke emission. It could also be inferred that by setting a proper SOI timing and dwell angle under two-stage injection scheme when suitable biodiesel blend is used, the engine performance could be optimized.